Determination of Selected Endocrine Disrupter Compounds at Trace Levels in Sewage Sludge Samples - Sonmez, Munire Selcen; Muz, Melis; Komesli, Okan Tarik; Bakirdere, Sezgin; Gokcay, Celal Ferdi (WILEY, 2012)
Simultaneous determination of endocrine disrupter compounds (EDCs), namely diltiazem, progesterone, benzylbutylphthalate (BBP), estrone, and carbamazepine (Cbz) were performed by using high performance LC-electrospray tandem MS. The ultrasound-aided sequential extraction of sludge samples was optimized to increase extraction efficiencies of the analytes; ranging between 93.0-98.3% recovery. The limit of detection values for diltiazem, progesterone, BBP, estrone, and Cbz were found as 0.78, 0.72, 0.24, 0.75, and 0.72 mu g/kg, respectively. Sludge samples taken from Ankara Tatlar; Hurma, Lara and Kemer of Antalya, and Middle East Technical University-vacuum rotating membrane wastewater treatment plant (WWTP) aeration tanks were analyzed for their EDCs contents under optimized conditions. Diltiazem was found in all the samples in the range between 116.4-180.8 ng/g while progesterone and estrone were not detected in any of the samples analyzed with the exception of Tatlar WWTP. The BBP concentration was between beyond detection and 9195.5 ng/g. In addition, Cbz was found in all the samples ranging from 25.6 to 118.8 ng/g.
Keywords: Extraction efficiency; Health risk; Ultrasound-aided sequential extraction; Wastewater treatment; Xenobiotic pollutant; PERSONAL CARE PRODUCTS; WASTE-WATER TREATMENT; SURFACE-WATER; PHARMACEUTICALS; ESTROGENS; SEDIMENTS; HORMONES; REMOVAL; PLANTS; FATE; Science & Technology - Other Topics; Environmental Sciences & Ecology; Marine & Freshwater Biology; Water Resources